Impact of Al-Rasheed Power Plant Effluents on Some Ecological characteristics of Tigris River, Southern Baghdad City - Fatema S. Muftin; Muhanned R. Nashaat; Raghd S. Rasheed; Kareem H. Ressan (Journal of Madenat Alelem University College, 2019)
This study was conducted for the period from January to December 2012 to investigate the effects of Al-Rasheed power plant (RPP) effluents on south of Baghdad at Al-Zafaraniya City on the some physical – chemical properties of the Tigris River. A water samples were collected monthly at four stations. Station one was located up to the power plant effluents, station two was located near the power plant effluents, station three was located 500 m down the power plant effluents and station four was located1000m down of the power plant effluents. The results showed an increase in water temperature of the stations near and below RPP ranging from 8 to 11.3 ºC compared with samples collected from the stations above RPP. The highest water temperature 38.3 ºC were recorded near the discharge area of RPP effluents on September. While, highest turbidity values were found at stations near of the RPP. Electrical conductivity, salinity and TDS near RPP are higher than other stations, these values reached to 1090 mS/cm, 0.69‰ and 0.54 g/L, respectively. The water from all stations was with weakly alkaline, but pH values were slightly increased at stations 2, ranging from 3.5 to 8.2. The maximum value of bicarbonate at stations 2 (190 mg/L) was recorded in December, with slightly increased were recorded values below RPP effluents. Lowest dissolved oxygen concentration (4.5 mg/L) was recorded during November near RPP effluents. Values of biological oxygen demand (BOD5) were distinctly higher near and below RPP. Whereas total hardness revealed a notable increase near and below RPP. However, peak concentration 900 mg/L was encountered in December at station 2. Calcium concentrations in general, were higher than those of magnesium and the highest values were recorded at down discharge point. Sulphate was the dominant among all ions. Its concentration at station up of RPP was 85 mg/L and elevated to 275 mg/L at stations near RPP effluents. Nitrate values at all stations were very moderate and ranged from 0.03 mg/L to 2.59 mg/L. Maximum phosphate concentration (6.8 mg/L P2O5 and 3 mg/L PO4-3) was recorded closer to discharge points. The results of this study conducted that there was a significant impact of the RPP effluents on increase of water temperature, turbidity and electrical conductivity, and there was an increase in the phosphate concentration and water hardness at station 2.